(untitled) (Journal of Applied Oral Science, 2016)
Objective: The aim of the present study was to evaluate and compare the cytotoxic effects of Biodentine and MTA on dental pulp stem cells (DPSCs) and to assess cell viability and adherence after material exposure to an acidic environment. Material and Methods: DPSCs were cultured either alone or in contact with either: Biodentine; MTA set for 1 hour; or MTA set for 24 hours. After 4 and 7 days, cell viability was measured using the MTT assay. Biodentine and MTA were also prepared and packed into standardized bovine dentin disks and divided into three groups according to the storage media (n=6/group): freshly mixed materials without storage medium (Group A); materials stored in saline (Group B); materials stored in citric acid buffered at pH 5.4 (Group C). After 24 hours, DPSCs were introduced in the wells and cell adherence, viability, and cellular morphology were observed via confocal microscopy after three days of culture. Cell viability was analyzed using repeated-measures analysis of variance test with Tukey's post hoc tests (α=0.05). Results: Biodentine expressed significantly higher cell viability compared with all other groups after 4 days, with no differences after 7 days. Notably, cell viability was significantly greater in 24-hour set MTA compared with 1-hour set MTA and control groups after 7 days. Material exposure to an acidic environment showed an increase in cell adherence and viability in both groups. Conclusions: Biodentine induced a significantly accelerated cell proliferation compared with MTA. Setting of these materials in the presence of citric acid enhanced DPSC viability and adherence.